Visible-Light-Induced Alkoxyl Radicals Enable α-C(sp(3))-H Bond Allylation - Zhang, Jing (iScience, 2019)
The alkoxyl radical is an essential reactive intermediate in mechanistic studies and organic synthesis with hydrogen atom transfer (HAT) reactivity. However, compared with intramolecular 1,5-HAT or intermolecular HAT of alkoxyl radicals, the intramolecular 1,2-HAT reactivity has been limited to theoretical studies and rarely synthetically utilized. Here we report the first selective 1,2-HAT of alkoxyl radicals for α-C(sp(3))-H bond allylation of α-carbonyl, α-cyano, α-trifluoromethyl, and benzylic N-alkoxylphthalimides. The mechanistic probing experiments, electron paramagnetic resonance (EPR) studies, and density functional theory (DFT) calculations confirmed the 1,2-HAT reactivity of alkoxyl radicals, and the use of protic solvents lowered the activation energy by up to 10.4 kcal/mol to facilitate the α-C(sp(3))-H allylation reaction.